Konservasi Lingkungan Ekowisata Bale Mangrove sebagai Pengembangan Eduwisata - Hidayat, Sugih Akbar; Ahmadin, Ahmadin; Nazifa, Syuhada; Ananda, Sri Devi; Fitri, Novita Mariana; Syukur, Abdul; Handayani, Baiq Sri; Sukma, Izza Melati (Universitas Mataram, 2025)
Mangrove ecosystems play an important role in maintaining the coastal environment and are useful as ecotourism, such as in Bale Mangrove Ecotourism, East Lombok. Although integrating conservation and education through ecotourism, its implementation is still not optimal due to the limited educational facilities that support mangrove learning. This community service aims to increase the potential of Bale Mangrove Ecotourism as a sustainable education center. Activities include mangrove identification, nursery, monitoring and planting. The results of the service showed that there were six mangrove species, such as Rhizophora mucronata and Avicennia marina which became educational information packaged in the form of mangrove mading, the planting of new mangrove seedlings of Rhizophora sp. as many as 100 seedlings and the addition of 20 new types of mangrove seedlings, namely Sonneratia sp., monitoring which is carried out once a month which shows that some of the mangroves that have been planted show quite good growth marked by supporting roots that begin to grow. It is hoped that this activity will continue to be carried out and implemented to become one of the attractions of education for visitors who visit.